Electrospun natural rubber fibers-based flexible conductive membranes - Dognani, Guilherme [UNESP]; da Silva, André Antunes [UNESP]; Cabrera, Flávio Camargo [UNESP]; Faita, Fabrício Luiz; Saénz, Carlos Alberto Tello [UNESP]; Bechtold, Ivan Helmulth; Job, Aldo Eloízo [UNESP]; Agostini, Deuber Lincon da Silva [UNESP] (FapUNIFESP (SciELO), 2020)
In recent years, the technique of electrospinning has been used to develop a novel class of micro-and nanoscale materials based on fibrous structures. Several polymers, in particular elastomers, that have been implemented in this process rely on properties such as elasticity, flexibility, biocompatibility, and low cost. Herein, we describe for the first time the electrospinning of natural rubber fibers without polymeric matrix to obtain self-standing non-woven mats and oriented elastomeric fibers. The fibers average diameters were approximately 5.5 µm. Polyaniline (PAni) was deposited on the membrane surface in order to enhance the conductive properties making easy the charge transportation. We have obtained biocompatible and flexible fibrous materials using natural rubber, this research opens up possibilities of using micro and nanofibers of only-natural rubber in many applications including sensors preparation.
Keywords: Electrospinning; Fiber technology; Microstructure; Polymer; Sensors